2020
DOI: 10.1097/iae.0000000000002589
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Paired-Eye Trial of Intravitreal Dexamethasone Implant for Cystoid Macular Edema in Retinitis Pigmentosa

Abstract: Purpose: To evaluate the efficacy and safety of intravitreal dexamethasone (DEX) implant in retinitis pigmentosa patients with cystoid macular edema (CME). Methods: In this randomized, noncontrolled, paired-eye, single crossover clinical trial, one eye of retinitis pigmentosa patients with bilateral CME with central macular thickness of >250 µm was randomized to intravitreal DEX implant while the fellow eye was observed. Both eyes were started on top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 36 publications
0
23
1
Order By: Relevance
“…The average change of CMT varied from −58.56– −320.62 μm after different local steroids treatments, as shown in Figures 6A,B . Moreover, in 2 comparative studies, intravitreal dexamethasone implant (0.7 mg, Ozurdex) showed better results in reducing CMT than the CAIs ( 14 , 16 ). Figure 7 is a representative of RP-CME treated with dexamethasone implant, illustrating the macular change by OCT during the treatment and follow-up [figure reproduced from Veritti et al ( 14 )].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…The average change of CMT varied from −58.56– −320.62 μm after different local steroids treatments, as shown in Figures 6A,B . Moreover, in 2 comparative studies, intravitreal dexamethasone implant (0.7 mg, Ozurdex) showed better results in reducing CMT than the CAIs ( 14 , 16 ). Figure 7 is a representative of RP-CME treated with dexamethasone implant, illustrating the macular change by OCT during the treatment and follow-up [figure reproduced from Veritti et al ( 14 )].…”
Section: Resultsmentioning
confidence: 96%
“…Two systematic reviews and one meta-analysis have been published regarding the treatment of RP-CME, with results of studies up to 2016 summarized and analyzed ( 4 , 8 , 12 ). Nevertheless, during the past 5 years, more evidence has been published on the application of CAIs ( 13 18 ), steroids ( 10 , 11 , 13 , 14 , 16 , 19 ), anti-VEGF therapy ( 20 ), and LASER treatment ( 21 ). Therefore, we conducted this updated systematic review and meta-analysis, to summarize the existing evidence on the treatment of RP-CME.…”
Section: Introductionmentioning
confidence: 99%
“…Table 2 summarizes characteristics and main outcomes of case reports or small series evaluating the efficacy and safety of DEX implant in RP [111][112][113][114][115]. Additionally, a couple of studies tried to elucidate the role of Dex implant in the treatment of CME secondary to RP [115,116]. Mansour et al, analyzed the outcomes of 45 eyes (34 patients) affected by CME secondary to RP treated with Ozurdex with a mean follow-up of 15.5 months [115].…”
Section: Evidence Of the Efficacy Of Dex In Inherited Retinal Disordersmentioning
confidence: 99%
“…Park et al, conducted a randomized, noncontrolled, paired-eye, single crossover clinical trial in which one eye of RP patients with bilateral CME was treated by Dex implant while the fellow eye was observed [116]. The authors treated 14 patients for 12 months and reported that Ozurdex could reduce the CME secondary to RP, but repeated injections were required in order to maintain the anatomical and functional results.…”
Section: Evidence Of the Efficacy Of Dex In Inherited Retinal Disordersmentioning
confidence: 99%
See 1 more Smart Citation